Deconstructing the Gecekondu - Jean-François Pérouse (European Journal of Turkish Studies, 2015)
This paper is a short, English version of the introducing paper of the thematic issue, originally in French: « Les tribulations du terme gecekondu (1947-2004) : une lente perte de substance. Pour une clarification terminologique », European Journal of Turkish Studies, Thematic Issue N°1 - Gecekondu, URL : http://ejts.revues.org/117